Ethnomedicinal values of Boerhaavia diffusa L. as a panacea against multiple human ailments: a state of art review - Das, Sarita; Singh, Puneet K.; Ameeruddin, Shaikh; Kumar Bindhani, Birendra; Obaidullah, Wajdi J.; Obaidullah, Ahmad J.; Mishra, Snehasish; Mohapatra, Ranjan K. (Frontiers in Chemistry, 2023)
Ethnopharmacological relevance: Therapeutic botanicals (plants and derivatives) are in use since antiquity for various health ailments. The ethnic community is the repository of the information, the multifactorial therapeutic applications of which may often need scientific validation. The spreading hogweed or Boerhaavia diffusa L., also known as Punarnava, is a reassuring medicinal herb with diverse pharmacological benefits. It is used in Ayurveda in Asia and Africa as a rejuvenator or 'Rasayan' for its excellent antiaging and antioxidant properties.The study aimed at compiling the state-of-art knowledge of the medicinal benefits of Boerhaavia diffusa L. and unraveling the unexplored commercially useful bioactive constituents by establishing their possible pharmacological benefits. Methods: The data from published literature, confined to pharmacological manifestations of various phytocomponents of Boerhaavia diffusa L. or its parts like root, leaf and stem were extracted from scientific databases, Google, Science Direct, PubMed, etc. using its antifungal, antibacterial, anticancer, anti-inflammatory, antidiabetic, hepatoprotective, cardioprotective, renoprotective, antifertility benefits and molecular docking study as search strings and keywords. Further, the reported in silico studies for bioactivity and bioavailability are detailed. Results: The botanicals possess numerous bioactive compounds, the most widely reported ones being phenolic (punarnavoside, trans-caftaric acid, boerhavic acid), rotenoid (boeravinones A-J), flavonoid (borhaavone, quercetin, kaempferol), isoflavonoid (2′-O-methyl abronisoflavone), alkaloid (punarnavine), steroid (boerhavisterol, β-Ecdysone), anthracenes and lignans (liriodendrin, syringaresinol monoβ-D-glucoside). Some of the reported reassuring benefits of their purified forms or even the crude extracts are antidiabetic, antimicrobial, anticancer, antioxidant, anti-inflammatory, hepatoprotective, renoprotective, cardioprotective, antifertility, etc. Conclusions: The article provides an extensive study on such pharmacological utility to support the ethnomedicinal use of Boerhaavia diffusa L. and propose possible mechanism of the various bioactive compounds in optimising metabolic dysfunctions, healing and protecting vital body organs, often related to the magnificent antioxidant property of this ayurvedic panacea. Further, establishing specific roles of its yet-to-explore bioactive constituents for diverse pharmacological applications is suggested.